Parent-Child Interaction Therapy (PCIT) for Disruptive Behavior in Children with and without ASD - Prawira, Michelle Angela; Yudiarso, Ananta (Psyche 165 Journal, 2025)
Children with ASD generally have behavioral problems significant. Without appropriate intervention, these behavioral problems can persist into adulthood and impact various aspects of life. Parent-Child Interaction Therapy (PCIT) is an effective behavior-based intervention for addressing disruptive behavior in children. However, meta-analytic research on its effectiveness, especially in children with Autism Spectrum Disorder (ASD), is still limited. This study aimed to evaluate the effectiveness of PCIT in reducing disruptive behavior and compare its effects between children with and without ASD using meta-analysis techniques. Articles from the past 10 years were collected through various databases using the PRISMA protocol. After the screening process, 10 studies with a pre-post control group design from various continents were obtained, involving a total of 418 child-parent pairs. Analysis of mean differences showed that PCIT was highly effective in reducing disruptive behavior in children with and without ASD (g = -0.938 [95% CI: -1.14, -0.73]). Although ASD and non-ASD status as moderators increased the effect size, the difference was not significant. Further investigation revealed that factors such as the child's intellectual level and receptive language skills significantly influence the effectiveness of PCIT, as this intervention requires parents to understand instructions. Results also suggest that PCIT implemented in a standardized clinical setting, with clear phases of therapy and independent practice for parents, tends to be more effective. Conversely, substantial modifications to PCIT implementation require further research to confirm its effectiveness. These findings confirm that PCIT is an effective intervention for reducing disruptive behavior and provide insights for future clinical practice.